REFORM OF PUBLIK SERVICE BUREAUCRACY LICENSING IN THE ADMINISTRATION OF LOCAL GOVERNMENTS IN REALIZING GOOD GOVERNANCE - Rohman, Asma’ur; Brahmasari, Ida Aju; Sukristyanto, Agus (DIA: Jurnal Administrasi Publik, 2023)
This study aims to describe and analyze: (1) Bureaucratic reform of investment licensing services in Sidoarjo (2) Quality of investment licensing in Sidoarjo (3) Increasing the value of investment realization in Sidoarjo (4) Supporting and inhibiting factors in carrying out investment licensing reform in Sidoarjo. The research uses a qualitative descriptive method with sources derived from informants and documents. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis used interactive model data analysis by collecting, reducing, presenting, and drawing conclusions. The results of the study show that: (1) Bureaucratic Reform of Licensing Services at DPMPTSP Sidoarjo is carried out by making improvements to the institutional and human resource aspects. (2) By reforming the bureaucracy for licensing services at DPMPTSP Sidoarjo, the quality of investment licensing services provided will increase (3) By reforming the bureaucracy for investment licensing services at DPMPTSP Sidoarjo it will also have an impact on increasing the amount of realized investment value. (4) While the supporting factors include the delegation of authority from the central government and the commitment and political will of the regional leadership of the Sidoarjo district, while the inhibiting factor in implementing this bureaucratic reform is the lack of overall delegation. The authority to issue SKPD sector permits is related to DPMPTSP and there is still a lack of cooperation between district and city regional governments and provincial governments. This study also provides recommendations regarding the need for increased authority in providing services and harmonious cooperation between district and city and provincial governments in creating a conducive investment climate.